Isolated cryptococcal osteomyelitis of the sacrum in an immunocompetent patient: a case report and literature review - Yanchun Zhong; Yuxi Huang; Di Zhang; Zhaoyuan Chen; Zhenxing Liu; Yongjun Ye (BMC Infectious Diseases, 2023)
Abstract Background Cryptococcus neoformans, an opportunistic fungal pathogen, seldom causes infection in immunocompetent people. Cryptococcal osteomyelitis is an uncommon condition in which Cryptococcus invades the bone. It usually occurs as part of a disseminated infection and rarely in isolation. The spine has been reported as the most common site of cryptococcal osteomyelitis; however, isolated case of sacrum involvement in immunocompetent patients has never been reported. Case presentation We report the case of a 37-year-old man without underlying disease who presented with progressive low back and sacrococcygeal pain. The patient was initially diagnosed with sacral tumour by a local doctor, and subsequently, after admission, was diagnosed with sacral tuberculosis. He was empirically treated with antitubercular drugs. The patient failed to respond to antitubercular drugs and complained of worsening low back pain. Additionally, he developed persistent radiating pain and numbness in his legs. For further diagnosis, we performed a computed tomography-guided puncture biopsy of the sacrum, which revealed granulomatous inflammation with massive macrophage infiltration and special staining revealed a fungal infection. We performed sacral debridement and drainage and obtained purulent specimens for pathological examination and microbial culture. Microbial identification and drug susceptibility tests revealed a Cryptococcus neoformans infection sensitive to fluconazole. Postoperatively, the persistent radiating pain and numbness in the legs resolved. After 12 consecutive weeks of antifungal therapy, all his symptoms resolved. The patient remained without any signs of recurrence at the 8-month follow-up. Conclusion We reported a rare case of isolated sacrum cryptococcal osteomyelitis in an immunocompetent patient. Furthermore, we identified and reviewed 18 published cases of spine cryptococcal osteomyelitis. Immunocompetent individuals are also at risk for cryptococcal osteomyelitis. Clinical manifestation and imaging are insufficient to diagnose cryptococcal osteomyelitis of the spine, and invasive examinations, such as puncture biopsy and fungal examinations, are needed. Antifungal therapy yields satisfactory results for the treatment of cryptococcal osteomyelitis of the spine, however, if the infective lesion is large, especially when it compresses the spinal cord and nerves, a regimen combining aggressive surgery with antifungal therapy is indispensable.